Teaching coordination in CLIL models (Journal of Parents and Teachers, 2013)
This article tries to clarify the role of coordinator teachers inside the organization of bilingual schools where CLIL (Content and Language Integrated Learning) is being implemented. These teachers´ profiles are key when tackling the coordination of content teachers, as the coordinators´ basic role is fostering and supporting dynamization strategies inside the teams involved in the bilingual teaching-learning processes in primary and in secondary education. The author shows guidelines about teaching professional competencies which should be taken into account to succeed in this undertaking.
Keywords: Coordinator teacher; CLIL; teacher team; team coordination; professional competencies